THU0276 Comparison of Two Different Scoring Methods for the Evaluation of Articular and Vascular FDG-PET/CT Uptake in PMR Patients. (9th June 2015) - Camellino, D.; Paparo, F.; Morbelli, S.; Cutolo, M.; Sambuceti, G.; Cimmino, M.A.
Abstract : Background: Polymyalgia rheumatica (PMR) is an inflammatory disease of the elderly characterized by girdle pain and systemic symptoms. Imaging techniques, such as 18F-fluorodesoxyglucose (FDG)-PET/CT, have demonstrated that inflammation is localized mainly in the joint capsule and in bursae, with possible associated large vessel vasculitis (1). 18F-FDG PET/CT readings of the intensity of the glucose analogue uptake in joints and vessels are scarcely standardized, however (2). Objectives: To compare a visual, semi-quantitative score for articular and vascular FDG uptake in PMR patients, with a quantitative one based on standardized uptake value (SUV). Methods: Eighty-four consecutive PMR patients, diagnosed according to Bird's criteria, underwent PET/CT after a standardized clinical examination. None of them fulfilled the ACR criteria for GCA. Joint and vascular uptake was scored both semi-quantitatively with a visual score and quantitatively. The visual score used a four-point scale (visual joint score, VJS and visual vascular score, VVS): 0=no uptake present, 1=uptake present but lower than liver uptake, 2=similar to liver uptake, 3=uptake higher than liver uptake. Regions of interest (ROIs) were drawn on the theoretical arterial wall and within the left ventricular chamber (blood-pool, BP). Arterial FDG uptake was quantified by calculating the mean standardized uptake value (SUV) within each ROI and the results expressed as the ratio between mean SUV value of each ROI and BP ROI (SUV/BP). To assess joint metabolism, CT-based ROIs were bilaterally drawn on joint and bursal spaces. The normal cut-off was derived from the mean+2SD of the SUV in each district of 84 sex- and age-matched controls: it was1.8 for joints and of 1.6 for arteries. Results: Results are reported in table 1 (see image 1). There was no correlation between sites of provoked pain at clinical examination and VJS or joint median SUV. Conclusions: Visual semi-quantitative and quantitative scores correlated only at joint level, but the percentage of positive areas was higher with the first method. Although a quantitative assessment could offer the theoretical advantage of being objective, reproducible and operator-independent, it underestimated both articular and vascular pathological findings. References: Camellino D, Cimmino MA. Imaging of polymyalgia rheumatica: indications on its pathogenesis, diagnosis and prognosis. Rheumatology (Oxford) 2012;51:77-86. Puppo C, Massollo M, Paparo F, Camellino D, Piccardo A, Shoushtari Zadeh Naseri M, Villavecchia G, Rollandi GA, Cimmino MA. Giant cell arteritis: a systematic review of the qualitative and semiquantitative methods to assess vasculitis with 18F-fluorodeoxyglucose positron emission tomography. Biomed Res Int. 2014. Epub 2014 Sep 1. Disclosure of Interest: None declared